Millennials’ Contribution in Disaster Risk Reduction: Case Study of Tidal Flooding in Semarang - Theresia Octastefani; Muhammad Rum (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This research focuses on the contribution of young millennials in reducing the risk of tidal flooding along the northern coast of Semarang. Young millennials have received special attention in disaster management, and the study of digital transformations in disaster management has become more significant. The objective of this study is to examine how smart disaster responses to natural disasters, specifically the case of tidal flooding in three districts of the city (North Semarang, Genuk, and Tugu) and a district nearby Demak Regency (Sayung). To obtain comprehensive results, this research uses qualitative methods, which data collected through in-depth interviews; Focus Groups Discussion (FGD); observations; and desk studies. This study finds that Millennials’ involvement is very important due to their distance from political interests and innovatively able to offer strategies in reducing the problems caused by tidal floods. The involvement of millennials in disaster management is relevant, given that Semarang will soon enjoy the demographic bonus, i.e. have a significant percentage of its population of productive age. Lastly, this research argues that vibrant public participation in disaster management can only be possible under democratic circumstances. As the implication, the study on public active participation might help disaster risk reduction campaign.